2016
DOI: 10.1021/acs.jpcc.6b06845
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of the Tensile Strength of Aged Cellulose Paper by Cholinium-Amino Acid Ionic Liquid Treatment

Abstract: In this study, a chemical stabilization method, that preserves the tensile strength of artificially aged paper pretreated with an aqueous solution of ionic liquid, is presented. Pure cotton cellulose paper samples were soaked with cholinium glycinate ionic-liquid solution either before or after the artificial aging process, which was based on thermal degradation in dry air. The tensile strength of artificially aged paper was measured by using the double-folding technique. The role of ionic liquids was investig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 55 publications
0
14
0
Order By: Relevance
“…One of the most striking applications is certainly in the domain of BCultural Heritage^and regards the use of cholinium glycine to stabilize the cellulose structure, preserve its tensile strength, and prevent its oxidation (Scarpellini et al 2016). Indeed, the study of mid-infrared spectra of artificially aged papers, non-treated and pre-treated with the IL, showed that the carbonyl peaks, that are used to quantify the degree of oxidation/acidification of cellulose, have lower intensity in ILpretreated samples than those in non-treated ones.…”
Section: And Old Paper Preservationmentioning
confidence: 99%
“…One of the most striking applications is certainly in the domain of BCultural Heritage^and regards the use of cholinium glycine to stabilize the cellulose structure, preserve its tensile strength, and prevent its oxidation (Scarpellini et al 2016). Indeed, the study of mid-infrared spectra of artificially aged papers, non-treated and pre-treated with the IL, showed that the carbonyl peaks, that are used to quantify the degree of oxidation/acidification of cellulose, have lower intensity in ILpretreated samples than those in non-treated ones.…”
Section: And Old Paper Preservationmentioning
confidence: 99%
“…The advantages in the synthesis of CAAILs are their byproduct water which can be used completely, and low cost of CAAILs compared to imidazolium-based ILs and other bio-based ILs prioritizes its application in biomolecular sciences. 34−36 Recently synthesized CAAILs have been used mostly in catalysis, old paper preservation, 37 biosensor, 38 and proton conduction, 39,40 In addition, ethidium bromide (EB) and 4′,6-diamidino-2phenylindole (DAPI) dyes (see Figure S4) were used that bind with DNA as intercalator and groove binder, respectively, to have a comparative understanding of the unique interaction of DNA with CAAILs. We hope this work will provide intriguing physical insights on the role of bio ILs for safe storage and application of DNA.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Indeed, cellulose polymers in elementary fibers assembly through H bonds in crystalline and disordered (amorphous) regions. Indeed, the monotonic increase of the absorption is typically observed in the THz spectra of amorphous solids by H-bond networks [20,41]. At the THz spectral regions these absorption spectra can be approximated by:…”
Section: Resultsmentioning
confidence: 99%